The Jessica cabin [videorecording (DVD)] - Critchlow, Riley Rose; Williamson, Chase, 1988-; Montgomery, Daniel; Montgomery, Daniel; Tranfo, Will (Freestyle Digital Media, 2023)
Nicky and his boyfriend Preston rent a cabin in the middle of the desert for a long, romantic weekend. Unbeknownst to them, they're being watched by two mysterious figures, ghosts Jackson and Taylor. Utterly bored with their afterlives (to a darkly comic degree), Jackson and Taylor quickly take a watchful liking to Nicky. After observing some questionable behavior from Preston, Jackson, and Taylor use their ghostly powers to intervene in the couple's relationship. A resulting argument between the couple leaves Nicky all alone at the cabin (with Jackson and Taylor, of course), and, fueled by loneliness, the ghosts make a reckless decision to ensure Nicky stays with them forever. The three souls now have to learn how to inhabit the cursed cabin together while navigating complicated feelings of resentment, regret, and attraction. As they reflect, revelations are made, dating back to the first spirit to haunt the cabin, the titular forlorn figure Jessica.